Modified nanocarbon surfaces for high performance supercapacitor and electrocatalysis applications1. Issue 71 (14th September 2015) - Es-Souni, Mohammed; Schopf, Dimitri
<x xml:space="preserve">Abstract</x> A supported porous nanocarbon film is heated slightly above the Leidenfrost temperature and directly transferred to an aqueous precursor solution of carbon nanotubes (CNTs) and Pt to form an adherent layer of Pt-NP decorated CNTs without the need for reducing agents.